THE IMPACT OF CREATIVE ACCOUNTING APPLICATIONS ON STOCK TRADING VOLUME: AN ANALYTICAL STUDY OF A SAMPLE OF JOINT-STOCK COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Alaa Mahdi Hadi; Ali Hussein Salman; Amal Abdul Hassan Kazem (Scholar Express Journals, 2023)
The research aims to shed light on creative accounting practices in financial reports and their impact on the trading volume in the Iraqi Stock Exchange. Starting from the problem of companies managing profits for the purpose of increasing the value of their shares at times and at other times reducing their profits in order to reduce the taxes they pay to the state. The research adopted the following main hypothesis: “Creative accounting practices affect the trading volume in the Iraqi Stock Exchange.” During the research, the reports of a group of companies listed in the market that obtained the highest trading volume during the research period were studied, and the Miller model was applied to reveal earnings management practices, which are considered one of Creative accounting methods, in addition to the income smoothing method. The researchers reached a set of conclusions, the most important of which is that all companies practice creative accounting in their issued financial statements, which affects the volume of trading in their name in the Iraqi Stock Exchange. A set of recommendations were reached, the most important of which is the use of the Miller model by auditors. Accounts for the purpose of revealing and measuring creative accounting practices in the companies whose accounts they audit.
Keywords: Creative accounting on stock trading volume